Validation of a spanish adaptation of a questionnaire for measuring nomophobia among university students - Roque Hernández, Ramón Ventura; Guerra Moya, Sergio Armando (John Wiley & Sons, 2022)
Smartphones are highly useful in contemporary society. However, their use can lead to problems, such as dependency and addiction. Nomophobia is a pathological fear of losing connectedness or not being able to access information or communicate with other people. The objectives of this study were to evaluate the four dimensions of the original version of the NMP-Q questionnaire by Yildirim and Correia using the Spanish version of the questionnaire developed by Gutiérrez-Puertas et al. Similarly, this research aims at assessing whether the questionnaire retains its four-dimensional structure when applied to a population of university students in the area of social sciences at a Mexican university. Using confirmatory and exploratory factor analysis techniques, we determined that nomophobia among the study population can be addressed through the first three dimensions of the original questionnaire, namely, not being able to communicate, losing connectedness, and not being able to access information. A fourth dimension, entitled “giving up convenience”, is mentioned in the literature. However, in this study, this dimension could not be clearly identified with the indicators included in the original questionnaire and was, therefore, omitted from the resulting questionnaire. Nomophobia is a modern phenomenon that is becoming increasingly prevalent in our society. Therefore, it must be studied and addressed. The nomophobia questionnaire presented in this article is a reliable way of taking measurements, as indicated by the research results. Further research should deepen the study of measuring nomophobia and improve the questionnaire through other indicators and conceptual dimensions that help explain this phenomenon in a precise and reliable way.